A comprehensive design model for integrating business processes in web applications. (4th December 2006) - Distante, Damiano; Rossi, Gustavo; Canfora, Gerardo; Tilley, Scott
Web applications have evolved from simple read-only websites to complex data- and operation-intensive systems. The main goal of this kind of application is to provide the users with services that assist them in carrying out activities according to a given set of business rules. The addition of transactions to modern web applications poses new challenges, such as managing the interplay between business process execution and navigation, and improving the user's experience in accessing the services that the web application offers. This paper presents a comprehensive design model for integrating business processes in web applications. The model is based on UWAT+, an extended and revised version of the Ubiquitous Web Applications (UWA) Transaction Design model for designing web transactions. UWAT+ makes it possible to design web application transactions according to the user's perspective and to integrate the web transaction design with the information and navigation design of the web application.